2013
DOI: 10.1016/j.ijheatmasstransfer.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced insulation temperature and the reduced thermal conductivity of nanostructured ceramic coating systems

Abstract: a b s t r a c tThe theoretical model on the size-dependent thermal conductivity of the nanograins and the composites, based on the phonon confinement and the boundary scattering effects, was developed to predict the 68% reduced thermal conductivity of the nanostructured ceramic coatings made of grains of 40-100 nm compared with the conventional ceramic coatings with micron-scale grains. In order to validate the model, the nanostructured zirconia layers and the corresponding conventional layers were sprayed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…2(c) in Ref. [24]), agreeing with the theoretical estimation. For the bulk splat grains of the conventional ceramic coatings, the diameter is the order of hundred microns and the thickness is about several microns [2].…”
Section: Sample Preparationsupporting
confidence: 87%
See 2 more Smart Citations
“…2(c) in Ref. [24]), agreeing with the theoretical estimation. For the bulk splat grains of the conventional ceramic coatings, the diameter is the order of hundred microns and the thickness is about several microns [2].…”
Section: Sample Preparationsupporting
confidence: 87%
“…The NiCrAlY interface bond coats of about 60 μm thickness, between the ceramic top coatings and the metallic matrixes, were obtained using the high velocity oxygen fuel process [24]. Two kinds of ceramic coatings were prepared by the similar process (Ar/H 2 ) on the Metco 7M atmospheric plasma spray equipment, and the METCO 9MP-DUAL type feedstock system was used.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lower thermal conductivity and the chemical stability of TBC at high temperatures, the underlying alloy can operate at higher temperatures with a longer service life. The advancement of engineering applications dictates that the top ceramic layer of TBC possesses lower thermal conductivity [6,7] and higher thermal shock resistance [8][9][10]. Nanostructured YSZ coatings from agglomerated nanoparticles have demonstrated competitive advantages in extending the performance of TBC by forming both a porous nano-zone [11] and cracks perpendicular to the coating surface that provide lower thermal conductivity, a lower thermal expansion coefficient and lower strain tolerance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al prepared a series of microencapsulated PCMs with binary cores and acrylate‐based copolymer shells and found that the wallboard fabricated with the synthesized microencapsulated PCMs showed an excellent thermal insulation performance . This can be attributed to the reduced thermal conductivity after encapsulation with copolymer shells, simply because the thermal insulation performance is positively correlated with a low thermal conductivity . Meanwhile, Ma et al investigated the reduced thermal conductivity of the polymer.…”
Section: Thermal Conduction Of Pcmsmentioning
confidence: 99%